20-Year trends in severe childhood asthma outcomes: Hospitalizations and intensive care visits. Issue 4 (2nd October 2018) - Radhakrishnan, Dhenuka; Dell, Sharon D.; Guttmann, Astrid; Shariff, Salimah Z.; To, Teresa
Abstract: RATIONALE: Few studies have examined trends in the rates of severe exacerbations of childhood asthma. OBJECTIVES: Our objective was to measure changes over time, and factors associated with severe asthma outcomes, namely hospitalizations and intensive care unit admissions among children. METHODS: This was a population-based retrospective multiple birth cohort study spanning the years 1996-2013. Health administrative data from the province of Ontario, Canada was used to assemble ten consecutive birth cohorts and identify children who were diagnosed with asthma between 0 and 8 years of age. Trends in the proportion of children hospitalized at the first diagnosis of asthma or admitted to intensive care units were quantified. Multivariable logistic regression was used to identify predictors of each outcome. MEASUREMENTS AND MAIN RESULTS: Of 1, 241, 060 Ontario-born children, 254, 964 were diagnosed with asthma. The proportion of children hospitalized at first asthma diagnosis decreased over time (5.81% to 4.44%, p -trend <0.0001). Asthma-intensive care unit admissions increased 7-fold (0.03% to 0.22%, p -trend <0.0001), and ventilation admissions increased 5-fold (0.02% to 0.1%, p -trend <0.0001). Younger age at diagnosis, male sex, comorbidities, lower socioeconomic status and rurality were significant predictors of asthma admissions; more pediatrician visits and higher neighbourhood ethnic concentration were protective. CONCLUSIONS: Although a smaller proportion of children over time are hospitalized at first asthma diagnosis, these admissions may be preventable among children with previous asthma-related healthcare encounters. This, along with increases in intensive care unit admission rates, suggests health care providers need to do more to prevent severe childhood asthma exacerbations.